INFORMATION SYSTEM POLICY INNOVATION FOR UNINHABITABLE HOUSES DATA COLLECTION PROGRAM (SIGAP-RTLH) IN GRESIK REGENCY - Indira arundina sari; Vidya Imanuari Pertiwi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
The existence of poverty conditions results in inequality in the quality of life such as inadequate nutrition, equitable distribution of health, education and lack of comfort in the places they live in. Uninhabitable houses are those that do not meet the requirements and standards. So, the Gresik Regency Government made a policy in the form of an innovation of the Uninhabitable House Data Collection Program Information System (SIGAP-RTLH) which is an information system for the RTLH Data Collection Program based on the web so that it is able to see the distance and time of data collection as well as updating the data up to date. locus in Gresik Regency. The research process is by collecting secondary data through observation, research results that have been published in indexed journals, credible census data and mass media reports that have valid credibility, such as the official website of the Kemenpan-RB, DJPB Ministry of Finance, Housing and Settlement Areas. The innovation of SIGAP-RTLH includes how to collect data, how to submit and product data collection for RTLH which can be accessed through a website that can be accessed anywhere at any time at http://sigaprtlh.gresikkab.go.id/index.php/login. The data product resulting from the SIGAP-RTLH update can be accessed as data collection material at the relevant government agencies as a way to facilitate data collection and follow-up to facilitate the handling of RTLH in the issuance of Building Construction Permits. Another benefit is to produce complete, valid, disaggregated, centralized, identified, integrated, uptodate, and accountable data collections. Policy Innovation The SIGAP-RTLH program is easy to implement or redesign for other agencies by developing services using the concept of an information system and has been proven to be accurate and precise and effective because it has received an innovation award at the national level.